Contexts, practices and concepts around Artistic and Cultural Mediation: research results developed by future professionals - Campos, Joana (2024)
This text seeks to contribute to the discussion around the professionalization and professionality of Artistic and Cultural Mediation (ACM) agents. The background for this discussion is based on theoretical references about professions, along with studies on artistic and cultural mediators. The analysis focuses on the training process developed within the scope of the degree in MAC at the ESELx-IPL, specifically in the Curricular Unit, Professionality and MAC, methodologically organized in two levels. In the first one, the curricular intentions of the UC are presented, within the framework of the course's training objectives. In the background, the research work carried out by the students, related to 4 academic years (between 2018/19 and 2021/22), is analyzed exploratoryly. The developed analysis allows knowing the questions and research problems chosen by the students, along with the broadening of knowledge about the profiles and professional practices in ACM, as well as the professional contexts. The exploratory analysis carried out allowed an approximation to issues related to the recognition and affirmation of ACM and (its) professionals, in different dimensions, concluding on the relevance of continuing the investigative practice in this scope, namely in the training of these professionals.